1997
DOI: 10.1002/(sici)1096-911x(199703)28:3<196::aid-mpo8>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a vancomycin solution to prevent bacteremia associated with an indwelling central venous catheter in neutropenic and non-Neutropenic cancer patients

Abstract: We evaluated the efficacy of a vancomycin solution in the prevention of bacteremia caused by vancomycin‐sensitive organisms (VSO) in cancer patients with a tunneled central venous catheter (CVC). Eighty‐three patients who had a single lumen CVC were randomized to use a heparin solution (25 U/ml) for daily catheter flush with (HepVan) or without (Hep) vancomycin, 25 mcg/ml. Febrile episodes were recorded, and central and peripheral blood cultures were drawn before beginning antibiotic therapy. Patients particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…Seven trials fulfilled inclusion criteria [85][86][87][88][89][90][91]. The characteristics of the included trials are shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven trials fulfilled inclusion criteria [85][86][87][88][89][90][91]. The characteristics of the included trials are shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that used this criteria, 4 evaluated a vancomycin-heparin lock solution [85,86,88,90], and the remainder evaluated a vancomycin-heparin flush solution. In 2 studies, after a specified time period, the lock solution was aspirated and discarded [85,86]; in the remaining 5 studies [87][88][89][90][91], the solution was flushed into the bloodstream.…”
Section: Resultsmentioning
confidence: 99%
“…72,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] The remaining six studies included citrate or taurolidine. [100][101][102][103][104][105]123 Most studies were conducted in patients undergoing haemodialysis (n = 17), but there were four studies in children with cancer.…”
Section: Resultsmentioning
confidence: 99%
“…[100][101][102][103][104][105]123 Most studies were conducted in patients undergoing haemodialysis (n = 17), but there were four studies in children with cancer. [85][86][87]100 No studies compared locks in adults or children receiving parenteral nutrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation